T cell progenitor therapy–facilitated thymopoiesis depends upon thymic input and continued thymic microenvironment interaction - Smith, M; Reichenbach, D; Parker, S; Riddle, M; Mitchell, J; Osum, K; Mohtashami, M; Stefanski, H; Fife, B; Bhandoola, A; Hogquist, K; Holländer, G; et al. (American Society for Clinical Investigatio, 2017)
Infusion of in vitro–derived T cell progenitor (proT) therapy with hematopoietic stem cell transplant aids the recovery of the thymus damaged by total body irradiation. To understand the interaction between proTs and the thymic microenvironment, WT mice were lethally irradiated and given T cell–deficient (Rag1-/-) marrow with WT in vitro–generated proTs, limiting mature T cell development to infused proTs. ProTs within the host thymus led to a significant increase in thymic epithelial cells (TECs) by day 21 after transplant, increasing actively cycling TECs. Upon thymus egress (day 28), proT TEC effects were lost, suggesting that continued signaling from proTs is required to sustain TEC cycling and cellularity. Thymocytes increased significantly by day 21, followed by a significant improvement in mature T cell numbers in the periphery by day 35. This protective surge was temporary, receding by day 60. Double-negative 2 (DN2) proTs selectively increased thymocyte number, while DN3 proTs preferentially increased TECs and T cells in the spleen that persisted at day 60. These findings highlight the importance of the interaction between proTs and TECs in the proliferation and survival of TECs and that the maturation stage of proTs has unique effects on thymopoiesis and peripheral T cell recovery.